Questions & Answers

Question

Answers

Answer

Verified

159.9k+ views

Hint: - Use the formula ${\left( {x - y} \right)^2} = {\left( {x + y} \right)^2} - 4xy$

Let the numbers be $x$ and $y$.

According to the question , the sum of two numbers is 8.

$ \Rightarrow x + y = 8...............\left( 1 \right)$

Reciprocals of the numbers be$\dfrac{1}{x}$and $\dfrac{1}{y}$

According to question 15 times the sum of reciprocals is also 8

$ \Rightarrow 15\left( {\dfrac{1}{x} + \dfrac{1}{y}} \right) = 8$

$ \Rightarrow 15\left( {\dfrac{{x + y}}{{xy}}} \right) = 8$

From equation 1

$

\Rightarrow 15\left( {\dfrac{8}{{xy}}} \right) = 8 \\

\Rightarrow xy = 15.........\left( 2 \right) \\

$

Now it is known fact that ${\left( {x - y} \right)^2} = {\left( {x + y} \right)^2} - 4xy$

Now from equation (1) and (2)

$

{\left( {x - y} \right)^2} = {8^2} - 4 \times 15 = 64 - 60 = 4 = {2^2} \\

\Rightarrow x - y = 2...........\left( 3 \right) \\

$

Now add equation (1) and (3)

$

\Rightarrow x + y + x - y = 8 + 2 \\

\Rightarrow 2x = 10 \\

\Rightarrow x = 5 \\

$

From equation 1

$

\Rightarrow x + y = 8 \\

\Rightarrow 5 + y = 8 \\

\Rightarrow y = 3 \\

$

So, the required numbers are 5 and 3.

Note: - Whenever we face such types of problems the key concept we have to remember is that always remember the formula ${\left( {x - y} \right)^2} = {\left( {x + y} \right)^2} - 4xy$. It will give us a simple approach to solve this kind of problem, then simplify we will get the required answer.

Let the numbers be $x$ and $y$.

According to the question , the sum of two numbers is 8.

$ \Rightarrow x + y = 8...............\left( 1 \right)$

Reciprocals of the numbers be$\dfrac{1}{x}$and $\dfrac{1}{y}$

According to question 15 times the sum of reciprocals is also 8

$ \Rightarrow 15\left( {\dfrac{1}{x} + \dfrac{1}{y}} \right) = 8$

$ \Rightarrow 15\left( {\dfrac{{x + y}}{{xy}}} \right) = 8$

From equation 1

$

\Rightarrow 15\left( {\dfrac{8}{{xy}}} \right) = 8 \\

\Rightarrow xy = 15.........\left( 2 \right) \\

$

Now it is known fact that ${\left( {x - y} \right)^2} = {\left( {x + y} \right)^2} - 4xy$

Now from equation (1) and (2)

$

{\left( {x - y} \right)^2} = {8^2} - 4 \times 15 = 64 - 60 = 4 = {2^2} \\

\Rightarrow x - y = 2...........\left( 3 \right) \\

$

Now add equation (1) and (3)

$

\Rightarrow x + y + x - y = 8 + 2 \\

\Rightarrow 2x = 10 \\

\Rightarrow x = 5 \\

$

From equation 1

$

\Rightarrow x + y = 8 \\

\Rightarrow 5 + y = 8 \\

\Rightarrow y = 3 \\

$

So, the required numbers are 5 and 3.

Note: - Whenever we face such types of problems the key concept we have to remember is that always remember the formula ${\left( {x - y} \right)^2} = {\left( {x + y} \right)^2} - 4xy$. It will give us a simple approach to solve this kind of problem, then simplify we will get the required answer.